Science of everyday things - Knight, Judson (The Gale Group, Inc, 2011)
This 4-vol. set illustrates the importance of scientific and mathematical principles through their use in everyday life. Each volume focuses on a specific scientific discipline -- biology, chemistry, earth sciences and physics -- offering students an in-depth understanding of each discipline and its theories. Creating a sense of real-life relevance for students, the Science of Everyday Things expands on the explanations of scientific principles and concepts using a straightforward, step-by-step approach, and presents theories in their everyday applications. Some of the entries covered include: how osmosis is used in dehydrating fruit; how the principles of aerodynamics are applied to cars; Charles' law and the chemical reaction that sets off an airbag; how algorithms are used to figure out the NCAA playoff tournaments; and more. Each volume the Science of Everyday Things presents approximately 40-50 entries and includes photos, diagrams, sidebars containing short glossaries and interesting facts and details relating to each principle.